Assessment of critical velocity in track and treadmill: physiological profiles and relationship with 3000-meter performance - Muller Pessôa Filho, D.; Denadai, B. S.; Reis Simionato, A.; Oliveira da Cruz Siqueira, L.; Aparecido Caritá, R.; Massini, D. A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
The present study aiming to verify the interference of different conditions (treadmill vs. track) on critical velocity (CV) values, as well as on the correlation to the 3000-meter performance (v3000m), and thus infer about the specificity of each values as training parameter for this distance. Seven runners (15.3±1.4 years) were submitted to a maximal progressive test (1.0 km×h-1 increments per minute until exhaustion) to assess VO2max and maximal aerobic velocity (vVO2max). Subsequently, CV was estimated from three running performances at each test condition, with exercise intensities adjusted for different time limits (tLim) at 900, 2100 and 3300 meters in track or at 90, 95 and 115% of vVO2max in treadmill. From linear adjustments, using stepwise method, CV was assessed on treadmill (CVTREADMILL) and track (CVTRACK), and both compared by the Mann-Whitney test. The sample-adjusted dispersion coefficient (R2 adj) analyzed the variance of v3000m with CVTRACK, CVTREADMILL and vVO2max. In all analyses, significance was set at P=0.05. In progressive test, VO2max reached 54.2±5.2 mLO2×kg-1×min-1 and vV?O2max reached 16.8±1.9 km×h-1. No differences were observed between CVTREADMILL and CVTRACK (14.0±1.8 vs. 12.3±3.2 km×h-1, P=0.46). Correlations were observed for v3000m with CVTREADMILL (R2 adj ~0.94), CVTRACK (R2 adj ~0.99) and vVO2max (R2 adj ~0.90), all showing P=0.001. It could be concluded that no influence was observe on the ability to achieve identical CV values from different assessment conditions. The correlation to the v3000 meters suggested better specificity of CVTRACK than CVTREADMILL for training prescription and performance control.